Dragon goes house-hunting. Volume 7 / Story by Kawo Tanuki ; art by Choco Aya ; translation, Nan Rymer ; adaptation, T Campbell. - Tanuki, Kawo; Campbell, T. (Seven Seas Entertainment, 2021)
Letty is a weak and cowardly dragon, but exaggerated legends about him spread like wildfire. There isn t anyone alive who hasn t heard the name Flame Dragon King, and Letty doesn t like that one bit. All he wants is a nice, safe place to live but as it turns out, he s not the only one searching. There s all sorts of house-hunters out there: the minions who took over the House of the Flame Dragon King, a circus troupe full of monsters, a World Serpent with a sense of wanderlust, and now, even a black dragon! Truly, no matter how different they might be, everyone dreams of a place to call home.